2001
DOI: 10.1046/j.1365-2141.2001.03103.x
|View full text |Cite
|
Sign up to set email alerts
|

β‐Spectrin Sta Bárbara: a novel frameshift mutation in hereditary spherocytosis associated with detectable levels of mRNA and a germ cell line mosaicism

Abstract: Hereditary spherocytosis (HS) is a common inherited anaemia characterized by the presence of spherocytic red cells and by a heterogeneous nature in terms of its clinical presentation, molecular basis and inheritance. Defects in several membrane protein genes have been involved in the pathogenesis of HS, including defects in the beta-spectrin gene. We detected a novel frameshift mutation in the beta-spectrin gene, a C deletion at codon 638, in a patient presenting with HS and spectrin deficiency. The mutant pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…On the other hand, it cannot be excluded that the truncated protein is degraded or its membrane incorporation is disturbed; in this case, only the normal, full‐length protein would be present in the cell membrane. This kind of situation was reported by Bassères et al (2001) who found that, in an HS subject with detectable levels of SPTB mRNA bearing a premature STOP codon, the mutant protein was undetectable in the erythrocyte membrane.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…On the other hand, it cannot be excluded that the truncated protein is degraded or its membrane incorporation is disturbed; in this case, only the normal, full‐length protein would be present in the cell membrane. This kind of situation was reported by Bassères et al (2001) who found that, in an HS subject with detectable levels of SPTB mRNA bearing a premature STOP codon, the mutant protein was undetectable in the erythrocyte membrane.…”
Section: Discussionsupporting
confidence: 53%
“…The G1408R substitution was first reported by Bassères et al (2001). Since the predicted glycine‐to‐arginine change could potentially be severe, we initially speculated that this genetic change might be responsible for spherocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…After a literature search related to HS, 50 cases including 31 ANK1 and 19 SPTB mutations were identified. These reports provided laboratory and clinical data, such as Hb level, splenectomy, and aplastic crisis which allowed calculation of the difference of Hb level according to mutated genes or the frequencies of splenectomy and aplastic crisis according to located domain of mutation in each gene.…”
Section: Resultsmentioning
confidence: 99%
“…Bassères DS et al reported a de novo frameshift mutation in the SPTB gene, and they supposed that the mutation might be caused by parental germline mosaicism without further confirmation. 15 In conclusion, mosaicisms pose challenging dilemmas for the diagnosis, prognosis and reproductive counseling of families with individuals affected by mosaic diseases. When parents have a child with constitutional, de novo occurrence of a disorder inherited in autosomal dominant pattern, parental germline or gonosomal mosaicisms must be considered, and they are at risk of passing on the same mutation to future children.…”
Section: Case Reportsmentioning
confidence: 99%